Problem Faced by Married Women in Higher Education: Challenges and Implications for Married Women in Pursuing Higher Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education is believed to provide knowledge and resource that hold potentials for economic empowerment for better livelihood and social development. Education is one of the most for reaching requirements for development, alleviating poverty, improving health outcomes and quality of life, reducing gender and social disparities and enhancing economic productivity. Education contributes to economic growth and productivity as well as sustains livelihood for national development.